CIVILIZATION AND CULTURE AS THE CATEGORIES OF SOCIAL-PHILOSOPHICAL ANALYSIS: N.Y. DANILEVSKY – K.N. LEONTIEV – N.A. BERDYAEV – P.A. SOROKIN - Стокалич, І. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The peculiarities of understanding of the civilization and culture of the Russian philosophy of the XIX-XX centuries.